What is Africa doing with the Novel? - Edward Sackey (Institute of African Studies - Carleton University, 2023)
The storyteller takes what he tells from experience—his own or that reported by others. And he in turn makes it the experience of those who are listening to his tale. The novelist has isolated himself. The birthplace of the novel is the solitary individual, who is no longer able to express himself by giving examples of his most important concerns, is himself uncounseled, and cannot counsel others. To write a novel means to carry the incommensurable to extremes in the representation of human life